Sex Disparity in Myopia Explained by Puberty Among Chinese Adolescents From 1995 to 2014: A Nationwide Cross-Sectional Study - Rongbin Xu; Rongbin Xu; Panliang Zhong; Catherine Jan; Catherine Jan; Catherine Jan; Yi Song; Xiuqin Xiong; Dongmei Luo; Yanhui Dong; Jun Ma; Randall S. Stafford (Frontiers Media S.A., 2022)
ImportanceGirls in East Asia have a higher myopia prevalence than boys. Less research has been done on whether girls' earlier puberty could explain this sex difference.ObjectiveThe purpose of this study was to evaluate the association between myopia and puberty and the role of puberty in explaining the sex disparity in adolescent myopia prevalence.Design, Setting, and ParticipantsIn this nationwide cross-sectional study, data came from five consecutive national surveys from 1995 to 2014 in China. We included 338,896 boys aged 11-18 and 439,481 girls aged 9-18.Main Outcomes and MeasuresMyopia was defined according to unaided distance visual acuity and subjective refraction; puberty status was defined dichotomously as menarche or spermarche status. The association between myopia and puberty was evaluated by robust Poisson GEE regression. Mediation analyses were used to quantify how much of the sex disparity in myopia could be explained by puberty.ResultsPost-menarche girls and post-spermarche boys showed 29-41% and 8-19% higher risk of myopia than pre-menarche girls and pre-spermarche boys, respectively. The association remained significant in girls [prevalence ratio (PR) = 1.07, 95%CI:1.04-1.10] but disappeared in boys (p > 0.05) after adjusting for potential confounders. Girls had a 12-23% higher risk of myopia than boys. A total of 16.7% of the sex disparity in myopia could be explained by girls' earlier puberty, whereas 11.1% could be explained by behavioral factors.Conclusion and RelevancePuberty status is independently associated with myopia in girls but not in boys. A significant proportion of the sex disparity in adolescent myopia could be explained by girls' earlier puberty, suggesting the need to consider sex-differentiated strategies for myopia prevention and treatment.